(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
Based on an analysis of the evolution of the legal regime of uneconomical tax foreclosures by professional councils, in light of the radical changes promoted by Law No. 14.195, of August 26, 2021, this article proposes a debate on the numerous controversial points that arise in its application, suggesting solutions to compose a historical, systematic and teleological interpretation, in order to give it concrete effectiveness in the sense of its legal and economic purpose, as well as honoring the constitutional principles of isonomy between professional councils, efficiency and reasonable duration of proceedings.